Análise da viabilidade de um projeto de aquisição de uma célula de soldagem robotizada - Dellay, Bruna Dal Castel (2021)
Investment in technologies and automated processes has been essential for companies in the agricultural sector, mainly taking into account cost reduction and process optimization. Given this context, this study aims to evaluate the economic viability of acquiring a robotic welding cell as one of the means of meeting future demands, in a company of agricultural machinery and implements located in the Northwest of Rio Grande do Sul. For this, the applied methodology was exploratory research, as a case study, where all the necessary data was evaluated so that it was possible to project in the most accurate way possible all the costs that involve the acquisition of a robotic welding cell in the standard established by the company, as well as the estimate of earnings with the investment. For this, economic engineering methods such as Net Present Value, Internal Rate of Return and Time to Return on Investment were used. Among the main results, there is a quick return on investment, given the gains in productivity, as well as the increase in capacity and automation of the welding process.